2009
DOI: 10.1016/j.iccn.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

To return or to discard? Randomised trial on gastric residual volume management

Abstract: SUMMARYBackground: The control of gastric residual volume (GRV) is a common nursing intervention in intensive care; however the literature shows a wide variation in clinical practice regarding the management of GRV, potentially affecting patients' clinical outcomes.The aim of this study is to determine the effect of returning or discarding GRV, on gastric emptying delays and feeding, electrolyte, and comfort outcomes in critically ill patients.Method: A randomised, prospective, clinical trial design was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 42 publications
(35 reference statements)
5
31
1
7
Order By: Relevance
“…They found no increase in complications and improved gastric emptying in adults who were re-fed GRs. 49 In addition, a very small RCT with 35 adults found no difference in complication rates between re-feeding and discarding GRs. 53 Unfortunately, no studies have been conducted regarding discarding or re-feeding GRs in infants.…”
Section: Should Gastric Residuals Be Discarded or Re-fedmentioning
confidence: 98%
See 1 more Smart Citation
“…They found no increase in complications and improved gastric emptying in adults who were re-fed GRs. 49 In addition, a very small RCT with 35 adults found no difference in complication rates between re-feeding and discarding GRs. 53 Unfortunately, no studies have been conducted regarding discarding or re-feeding GRs in infants.…”
Section: Should Gastric Residuals Be Discarded or Re-fedmentioning
confidence: 98%
“…48,49 In a small study of NICU nurses, only 4% consistently re-fed aspirated GRs. 48 If GRs are discarded, important elements including hydrochloric acid and pepsin may also be lost.…”
Section: Should Gastric Residuals Be Discarded or Re-fedmentioning
confidence: 99%
“…Therefore, precautionary cessation of EN when GRV < 400–500 mL should be eradicated from practice (McClave and Snider, , Woien and Bjork, ). However, in an randomized controlled trial (RCT) by Juvé‐Udina et al (), 125 critically ill patients assigned to examine the effectiveness of ‘reintroducing gastric contents’ when GRV is 250 mL or more. This protocol led to maintaining GRVs closer to the physiological level, and minimizing complications.…”
Section: Introductionmentioning
confidence: 99%
“…This protocol led to maintaining GRVs closer to the physiological level, and minimizing complications. Although re‐introducing GRV is accepted up to 300 mL, additional amounts may cause electrolyte imbalance (Juvé‐Udina et al , , McClave et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Others advocate the initiation of prokinetic agents or conversion to small bowel feedings. 7 What if a GRV can't be obtained? A randomized, prospective trial of critically ill patients showed those who had GRVs of up to 250 mL reinstilled had no greater incidence of NG-tube obstructions, pulmonary aspiration, gastrointestinal (GI) intolerance episodes, or enteral feeding delays than those whose GRVs were discarded.…”
Section: Grv Dilemmasmentioning
confidence: 99%